Molecular Cloning, Characterization, and Anti-avian Pathogenic Escherichia coli Innate Immune Response of the Cherry Valley Duck CIITA Gene - Li, Rong; Guo, Mengjiao; Lin, Jing; Chai, Tongjie; Wei, Liangmeng (Frontiers in Microbiology, 2017)
Class II major histocompatibility complex (MHC-II) transactivator (CIITA) is a member of the pattern recognition receptor in cytoplasm, which is involved in host innate immune responses. In this study, the full-length cDNA of Cherry Valley duck CIITA (duCIITA) was cloned from the spleen of healthy Cherry Valley ducks for the first time. The CDs of duCIITA have 3648 bp and encode 1215 amino acids. The homology analysis of CIITAs amino acid sequence showed that the duCIITA has the highest identity with the Anas platyrhynchos (94.9%), followed by Gallus gallus and Meleagris gallopavo. Quantitative real-time PCR analysis indicated that duCIITA mRNA has a broad expression level in healthy Cherry Valley duck tissues. It was highly expressed in the lung and cerebellum, and lowly expressed in the rectum and esophagus. After the avian pathogenic Escherichia coli (APEC) O1K1 infection, the ducks exhibited the typical clinical symptoms, and a severe fibrinous exudate in the heart and liver surface was observed. Meanwhile, a significant up-regulation of duCIITA was detected in the infected liver. The inflammatory cytokines IL-1β, IL-6 and IL-8 have a significant up-regulation in the infected liver, spleen and brain. In addition, knockdown of the duCIITA reduces antibacterial activity and inflammatory cytokine production of the duck embryo fibroblast cells. Our research is the first study of the cloning, tissue distribution, and antibacterial immune responses of duCIITA, and these findings imply that duCIITA was an important receptor, which was involved in the early stage of the antibacterial innate immune response to APEC O1K1 infection of Cherry Valley duck.